2011
DOI: 10.1161/circulationaha.111.034793
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Extracorporeal Removal of Soluble Fms-Like Tyrosine Kinase 1 in Preeclampsia

Abstract: Background-Targeted therapies to stabilize the clinical manifestations and prolong pregnancy in preeclampsia do not exist. Soluble fms-like tyrosine kinase 1 (sFlt-1), an alternatively spliced variant of the vascular endothelial growth factor receptor 1, induces a preeclampsia-like phenotype in experimental models and circulates at elevated levels in human preeclampsia. Removing sFlt-1 may benefit women with very preterm (Ͻ32 weeks) preeclampsia. Methods and Results-We first show that negatively charged dextra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
220
0
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 310 publications
(237 citation statements)
references
References 55 publications
(56 reference statements)
5
220
0
12
Order By: Relevance
“…The cause of preeclampsia is thought to involve release of a soluble fms-like tyrosine kinase (a vascular endothelial growth factor receptor) from placenta leading to decreased bioavailability of circulating vascular endothelial growth factor and endothelial injury, decreased NO formation, vasoconstriction, and glomerular damage with endotheliosis. 11,12 Preeclamptic (PE) patients exhibit suppressed renin-angiotensin-aldosterone system activity, in particular aldosterone, 13,14 and avid NaCl retention. 15 Treatment with furosemide in preeclampsia yields less stimulation of plasma renin concentration.…”
mentioning
confidence: 99%
“…The cause of preeclampsia is thought to involve release of a soluble fms-like tyrosine kinase (a vascular endothelial growth factor receptor) from placenta leading to decreased bioavailability of circulating vascular endothelial growth factor and endothelial injury, decreased NO formation, vasoconstriction, and glomerular damage with endotheliosis. 11,12 Preeclamptic (PE) patients exhibit suppressed renin-angiotensin-aldosterone system activity, in particular aldosterone, 13,14 and avid NaCl retention. 15 Treatment with furosemide in preeclampsia yields less stimulation of plasma renin concentration.…”
mentioning
confidence: 99%
“…In line with this notion, a recent study suggested an apheresis based treatment for reduction of plasma levels of a placental protein Flt-1, whose elevated levels are detrimental for normal pregnancy [35]. The statement of Goske et al, raises hopes about enhanced treatment options for PE, relative to the present situation of administering drugs with potent side-effects.…”
Section: Current Therapeutic Interventions For Pementioning
confidence: 97%
“…Une autre piste pourrait être fournie par l'administration de nanoparticules ciblant le trophoblaste [45], qui pourrait véhiculer des siARN (en anglais, small interfering RNA) mimant l'action des miARN naturels. Récemment, il a été proposé de limiter la circulation de sFLT1 pour permettre une prolongation de la grossesse dans des conditions satisfaisantes de sécurité pour la mère et le foetus [46]. Jusqu'à présent, ces études ont concerné très peu de patientes.…”
Section: Nouvelles Drogues Nouveaux Modes D'applicationunclassified